"Me ajuda aqui!" A expressão do imperativo em Revistas da Turma da Mônica na segunda década do século XXI - Conceicao, Ednaildes Bispo da (2022)
Normative grammars register the grammatical imperative (deixa/deixe) based on the pronominal context and the context of the polarity of the structure: in affirmative sentences, with indicative morphology (deixa/diz/vai), in the discursive context of the pronoun tu; with subjunctive morphology (deixe/diga/vá), in the discursive context of the pronoun você. In negative sentences, on the other hand, the imperative must always be associated with the subjunctive mode, regardless of the pronominal context (CEGALLA, 1991, p. 186-187). However, research carried out on the subject has found a reality several times different from that registered by the grammatical tradition, since the imperative forms are also carried out with significant percentages of indicative depending, to a large extent, on geographic aspects of the spoken and written samples considered (cf., por exemplo, ALVES, 2008, 2009, CONCEIÇÃO, 2017, OLIVEIRA, 2017, SAMPAIO, 2002, SCHERRE, 2003, 2004, 2005, 2012). Based on this, this research analyzes the variation in the expression of the imperative (deixa/deixe) in 79 comic books from Monica and Friends published in 2017, 2018 and 2019. Our objective, therefore, is to analyze the behavior of the expression of the imperative in these comics and compare it with results of previous research (CONCEIÇÃO, 2017; SCHERRE, 2003, 2004, 2005, 2012). Our results showed a robust percentage of 74.5% of imperative associated with the indicative. In other words, we analyzed a grand total of 2,414 data, with 2,348 variable occurrences and 1,750 data associated with the indicative form. Our variables selected by the statistical tool, in order of selection, were: structure polarity and pronominal context; phonic salience; characters; presence/absence, type, subject pronoun and position of the unstressed pronoun in relation to the verb; speech acts, according to Faraco (1986); number of syllables of the verb in the infinitive form; presence/absence and position of the vocative in relation to the verb. The variables not selected and eliminated by the program, in order of elimination, were: year of publication; presence and absence of deictics; and verb conjugation. The research is based on the Theory of Linguistic Variation and Change (LABOV, 2008[1972], MOLLICA; BRAGA, 2012, WEINREICH; LABOV; HERZOG, 1968); and we performed the statistical treatment of data using Goldvarb X (GUY; ZILLES, 2007, SANKOFF; TAGLIAMONTE; SMITH, 2005).